PENGARUH PERKEMBANGAN PARIWISATA TERHADAP KONDISI EKONOMI MASYARAKAT DI KAWASAN GILI AIR, PROVINSI NTB - Adam Maryona; Baiq Rizka Milania Ulfah; Muhamad Sayuti; Mimi Cahayani (Yayasan Nusantara Hasana Berdikari, 2026)
The development of the tourism sector is an important factor in encouraging economic growth in local communities, including in the Gili Air area, North Lombok Regency. The increase in the number of tourists and the development of tourist facilities is thought to have an impact on changes in the economic conditions of the community, such as increasing income, job opportunities and shifts in livelihoods. However, these benefits are not always felt equally by all levels of society. This research aims to analyze the influence of tourism development on the economy of the Gili Air community. The method used is a descriptive qualitative approach with data collection techniques through interviews, observation and documentation. Research informants consist of local communities who are directly or indirectly involved in the tourism sector. The research results show that tourism development has had a positive impact in the form of increasing income, opening up employment opportunities, and developing community micro-enterprises. However, there are also negative impacts such as economic inequality and dependence on the seasonal tourism sector. The conclusion of this research is that tourism development has a significant impact on the economy of the Gili Air community, but more inclusive and sustainable management is needed so that the benefits can be felt equally by the entire community.